2021
DOI: 10.1128/mra.01410-20
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of Streptomyces sp. Strain HB-N217, Isolated from the Marine Sponge Forcepia sp.

Abstract: The genome sequence of the Forcepia sponge-derived bacterium Streptomyces sp. strain HB-N217 was determined, with approximately 8.25 Mbp and a G+C content of 72.1%. Thirty biosynthetic gene clusters that bear the capability to produce secondary metabolites were predicted. The results will aid marine natural product chemistry and sponge-microbe association studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
2
2
0
Order By: Relevance
“…This finding is consistent with the study of Xavier et al (2021) who analysed the genomic DNA of Streptomyces sp. NA03103 using anti-SMASH v5.2.0 and found a number of predictive BCGs which may implicate diverse secondary metabolic biosynthesis, such as polyketides, nonribosomal peptides, terpenes, and lanthipeptides (Xavier et al, 2021). Further experiments are required to investigate the function of this potential bacterial strain on the synthesis of marine natural products.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding is consistent with the study of Xavier et al (2021) who analysed the genomic DNA of Streptomyces sp. NA03103 using anti-SMASH v5.2.0 and found a number of predictive BCGs which may implicate diverse secondary metabolic biosynthesis, such as polyketides, nonribosomal peptides, terpenes, and lanthipeptides (Xavier et al, 2021). Further experiments are required to investigate the function of this potential bacterial strain on the synthesis of marine natural products.…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have reported the biological activities of benzoxazine derivatives in various aspects, including antiinflammatory, antimicrobial, anticancer and antimalaria (Akhter et al, 2011;Foto et al, 2014;Sharma et al, 2018). This finding is consistent with the study of Xavier et al (2021) who analysed the genomic DNA of Streptomyces sp. NA03103 using anti-SMASH v5.2.0 and found a number of predictive BCGs which may implicate diverse secondary metabolic biosynthesis, such as polyketides, nonribosomal peptides, terpenes, and lanthipeptides (Xavier et al, 2021).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…strain HB-N217 (isolated from a marine sponge, Forcepia sp. in the USA) [77], Streptomyces sp. CCM_MD2014 (soil isolate from the USA) [78], Streptomyces sp.…”
Section: Resultsmentioning
confidence: 99%